Kegagalan Diplomasi Koersif Arab Saudi terhadap Qatar - Febriandi Febriandi (Indonesian Journal of International Relations, 2018)
Saudi Arabia along with Bahrain, the United Arab Emirates and Egypt suddenly cut off their diplomatic relations with Qatar. Allegations of Qatar's active participation in supporting terrorism have led to this decision. Saudi Arabia and allies carried out a blockade of land, sea and air and then submitted 13 conditions to Qatar. Qatar firmly refused to comply with Saudi’s demands. This paper will discuss the factors of failure of coercive diplomacy carried out by Saudi Arabia and allies against Qatar. As for supporting the author's analysis, this paper will use the theory of coercive diplomacy by Alexander L. George.